2008
DOI: 10.1002/adfm.200800428
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant‐Free, Self‐Assembled PVA‐Iron Oxide/Silica Core–Shell Nanocarriers for Highly Sensitive, Magnetically Controlled Drug Release and Ultrahigh Cancer Cell Uptake Efficiency

Abstract: Surfactant‐free, self‐assembled iron oxide/silica core–shell (SAIO@SiO2) nanocarriers were synthesized as bifunctional magnetic vectors that can be triggered for the controlled release of therapeutic agents by an external magnetic field. In addition, drug release profiles can be well‐regulated through an ultrathin layer of silica shell. The hydrophobic drug molecules were encapsulated within the iron oxide‐PVA core and then further covered with a thin‐layer silica shell to regulate the release pattern. Remote … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…Magnetic fluid hyperthermia is a type of cancer therapy in which cancer cells are killed by raising the cell temperature above 44°C, utilizing the heat dissipated from magnetic nanoparticles [43,44]. Recently, the use of magnetic sensitive hydrogels has been explored for hyperthermia applications [45][46][47][48].…”
Section: Hyperthermia Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic fluid hyperthermia is a type of cancer therapy in which cancer cells are killed by raising the cell temperature above 44°C, utilizing the heat dissipated from magnetic nanoparticles [43,44]. Recently, the use of magnetic sensitive hydrogels has been explored for hyperthermia applications [45][46][47][48].…”
Section: Hyperthermia Studiesmentioning
confidence: 99%
“…Furthermore, hydrogels can be modified with new functional groups or prepared as composites to increase their metal absorption capacity and their versatility for practical usage [39,40]. Similarly magnetic separation has become a promising method for environmental purification as it produces no contamination and can easily separate toxic metals from the aqueous medium under applied magnetic field [37,[41][42][43][44]. Hence, hydrogels with magnetic properties have become a new class of intelligent materials which attract interest as absorbents for the removal of toxic materials from the aquatic media [39].…”
Section: Metal Absorption Studiesmentioning
confidence: 99%
“…Magnetic nanoparticles (MNPs) are currently being intensively investigated because of their extensive applications such as drug release [1][2][3][4], magnetic resonance imaging [5][6][7][8], biological separation [9,10] and water purification [11,12]. Among them, water purification with magnetic materials is a new research subject, which was reported by only a few papers.…”
Section: Introductionmentioning
confidence: 99%
“…Much attention has been devoted recently to well-dispersed magnetic colloidal particles, owing to the broad range of potential applications in the fields of ferrofluids, 1,2 high-density data storage, 3 disks and toner in printing, [4][5][6] magnetic resonance imaging, 7,8 enzyme immobilization, 9 rapid biological separation, 10,11 drug delivery, [12][13][14] biomedical materials, [15][16][17] immunoassays 18,19 and biosensors. 20,21 The development of colloidal-stable magnetic nanoparticles is essential from a practical point of view.…”
Section: Introductionmentioning
confidence: 99%